Held Up in Traffic—Defects in the Trafficking Machinery in Charcot-Marie-Tooth Disease - Markworth, Ronja; Bähr, Mathias; Burk, Katja (Frontiers in Molecular Neuroscience, 2021)
Charcot-Marie-Tooth disease (CMT), also known as motor and sensory neuropathy, describes a clinically and genetically heterogenous group of disorders affecting the peripheral nervous system. CMT typically arises in early adulthood and is manifested by progressive loss of motor and sensory functions; however, the mechanisms leading to the pathogenesis are not fully understood. In this review, we discuss disrupted intracellular transport as a common denominator in the pathogenesis of different CMT subtypes. Intracellular transport via the endosomal system is essential for the delivery of lipids, proteins and organelles bidirectionally to synapses and the soma. As neurons of the peripheral nervous system are amongst the longest neurons in the human body, they are particularly susceptible to damage of the intracellular transport system, leading to a loss in axonal integrity and neuronal death. Interestingly, defects in intracellular transport, both in neurons and Schwann cells, have been found to provoke disease. This review explains the mechanisms of trafficking and subsequently summarizes and discusses the latest findings on how defects in trafficking lead to CMT. A deeper understanding of intracellular trafficking defects in CMT will expand our understanding of CMT pathogenesis and will provide novel approaches for therapeutic treatments.